Машинно-трансформаторний агрегат для вітроенергетичних установок - Панченко, В.І.; Ципленков, Д.В.; Гребенюк, А.М.; Кириченко, М.С.; Бобров, О.В. (Електротехніка і електромеханіка, 2016)
В роботі запропонована нова конструкція індукторної електричної машини, яка в технічній літературі називається
– машинно-трансформаторним агрегатом (МТА). Для такого агрегату отримано співвідношення для визначення розрахункової потужності. На конкретному прикладі показано, що при однакових габаритах розрахункова потужність
МТА може перевищувати таку для звичайних синхронних машин. Конструкція МТА дозволяє розмістити котушки
обмотки статора на деякій відстані від рухомих елементів машини, а саме, у закритій ємності, заповненій електроізоляційною рідиною. Це дасть змогу збільшити потужність за рахунок більш ефективного охолодження обмотки, а
також підвищити вихідну напругу МТА як генератора до рівня 35 кВ і більше. В работе предложена новая конструкция индукторной электрической машины, которая в технической литературе
называется – машинно-трансформаторный агрегат (МТА). Для такого агрегата получено соотношение для определения расчетной мощности. На конкретном примере показано, что при одинаковых габаритах расчетная мощность МТА
может превышать таковую для обычных синхронных машин. Конструкция МТА позволяет разместить катушки обмотки статора на некотором расстоянии от подвижных элементов машины, а именно, в закрытой емкости, заполненной электроизоляционной жидкостью. Это позволит увеличить мощность за счет более эффективного охлаждения
обмотки, а также повысить выходное напряжение МТА как генератора до уровня 35 кВ и более. Background. Electric generators of wind turbines must meet the
following requirements: they must be multi-pole; to have a minimum size and weight; to be non-contact, but controlled; to ensure the maximum possible output voltage when working on the
power supply system. Multipole and contactless are relatively
simply realized in the synchronous generator with permanent
magnet excitation and synchronous inductor generator with
electromagnetic excitation; moreover the first one has a disadvantage that there is no possibility to control the output voltage,
and the second one has a low magnetic leakage coefficient with
the appropriate consequences. Purpose. To compare machine
dimensions and weight of the transformer unit with induction
generators and is an opportunity to prove their application for
systems with low RMS-growth rotation. Methodology. A new
design of the electric inductor machine called in technical literature as machine-transformer unit (MTU) is presented. A
ratio for estimated capacity determination of such units is obtained. Results. In a specific example it is shown that estimated
power of MTU may exceed the same one for traditional synchronous machines at the same dimensions. The MTU design
allows placement of stator coil at some distance from the rotating parts of the machine, namely, in a closed container filled
with insulating liquid. This will increase capacity by means of
more efficient cooling of coil, as well as to increase the output
voltage of the MTU as a generator to a level of 35 kV or more.
The recommendations on the certain parameters selection of the
MTU stator winding are presented. The formulas for copper
cost calculating on the MTU field winding and synchronous
salient-pole generator are developed. In a specific example it is
shown that such costs in synchronous generator exceed 2.5
times the similar ones in the MTU